Advancing big data analytics for healthcare service delivery - Iyamu, Tiko (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"In recent years, there has been steady increase in the interest shown in both big data analytics and the use of technology to improve healthcare services. Despite the growing interest, there are limited materials to address the needs and challenges posed. This book aims to technologically advance the deployment and use of big data analytics to increase patients' big data usefulness and improve healthcare service delivery. The book provides significant insights and useful guide on how to access and manage big data, in improving healthcare service delivery. The book contributes fresh perspective, which primarily comes from the complementary use of analytics approach with actor-network theory (ANT), and other techniques, in advancing healthcare service delivery. accessing and managing healthcare big data have always been a challenging exercise. Due to the sensitivity of the health sector, the focus on patients' big data was either from technical or social perspective. This book employs sociotechnical theories, ANT and structuration theory (ST) as lenses to examine and explain the factors that enable and constraint the use of patients' big data for health services. By doing so, the book brings different dimension and advance health service delivery. Providing a timely and important contribution to this critical area, this book is a valuable, international resource for academics, postgraduate students and researchers in the areas of information technology (IT), big data analytics, data management and health informatics"--
Healthcare data management : structuration view -- Open technology innovation for healthcare services -- Interaction with cloud-hosted health data -- A framework for selecting healthcare big data analytics tools -- Interpretivist and analytics approaches for healthcare big data analytics -- A multi-level approach for healthcare big data analysis -- Transforming big data for service delivery -- Integration of social media with healthcare big data for services -- Actor-network theory view of healthcare big data -- Implementation of big data analytics for healthcare services -- Evaluating big data analytics tools for healthcare services.
OCLC-licensed vendor bibliographic record.
Keywords: Medical informatics -- Data processing; Medical care -- Data processing; Medical care -- Technological innovations; Big data; Data mining